2015
DOI: 10.5198/jtlu.2015.750
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Dubai Metro on the value of residential and commercial properties

Abstract: This paper analyzes the impact of the newly operated Dubai Metro on the sale transaction value of dwellings and commercial properties. The effect is estimated for properties within different catchment zones of a metro station using difference-in-differences and hedonic pricing methods on both repeated cross-sectional data and pseudo panel data. Our estimates show a positive effect of the metro on sale values of both residential and commercial properties, although the effect is stronger for commercial propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 42 publications
(99 reference statements)
4
59
0
3
Order By: Relevance
“…In a case study of the Hiawatha Light Rail Transit, Ko and Cao () found that light rail transit (LRT) induced significant price premiums for commercial and industry properties, and the price premium extended to 0.9 miles away from LRT. A recent study of Dubai rail system found price premium reached its peak between 701 and 900 metres for commercial properties (Mohammad et al ). Nelson et al () found in both Dallas, Texas and Denver, Colorado that price premium of office rent extended 1.85‐mile from rail station, with a substantial price premium of 25 per cent within the first 1‐mile.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a case study of the Hiawatha Light Rail Transit, Ko and Cao () found that light rail transit (LRT) induced significant price premiums for commercial and industry properties, and the price premium extended to 0.9 miles away from LRT. A recent study of Dubai rail system found price premium reached its peak between 701 and 900 metres for commercial properties (Mohammad et al ). Nelson et al () found in both Dallas, Texas and Denver, Colorado that price premium of office rent extended 1.85‐mile from rail station, with a substantial price premium of 25 per cent within the first 1‐mile.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Property value studies generally use hedonic pricing, increasingly as part of a spatial lag model (e.g., Wang et al, 2016;Xu et al, 2016) or a before and after comparison using repeat sales (Chatman, Tulach, and Kim, 2012;Kim and Lahr, 2014;Dubé et al, 2011Dubé et al, , 2013. A few studies use a differencein-differences quasi-experimental model to account for unobservable characteristics (Bajic, 1983;Gib-bons and Machin, 2005;Dubé et al, 2011Dubé et al, , 2013Mohammad et al, 2017). This research builds off the quasi-experimental work, identifying a control group and testing the treatment effects of transit construction on businesses.…”
Section: Rising Property Valuesmentioning
confidence: 99%
“…In the first model, the control group is any property farther than 0.5 km, in the second, farther than 1 km, and so forth. This paper adopts the multiple rings method from Mohammad et al (2017) but lessens the initial distance. The shorter distances reflect the paper's focus on construction rather than property values.…”
mentioning
confidence: 99%
See 2 more Smart Citations